Planning of microcycle in football- dosaging of the training load - #2 - Vuksanovikj, Vladimir; Nestorova, Mihaela; Tasevski Zikica; Aceski, Aleksandar; Brazhanski Ognen; Spasovska, Katerina (Faculty of physical education sport and health, 2021)
In the process of planning/ modeling training programs, repetitive training periods are used, in the form of cycles (weekly, monthly, annual). This is done in order for the coach to present clearly the idea for the training program, and also to allow the athlete's biorhythm to adapt to the competition’s cycles. When creating a training cycle in football, the components of the training such as intensity, volume, weekly training frequency as well as rest, during and after the training, are always taken into account. We usually talk about the 7-day micro cycle, as the shortest period of planning the training program. This micro cycle can be organised in several variants: in the preparatory period, or in the period of competition, where there can be one or two matches in seven days.
Планирање на микроциклус во фудбал- дозирање на тренинг оптоварување: - # 2
Keywords: microcycle,; training,; dosing,; intensity,; rest